The Second Laminin G-type Domain of Protein S Is Indispensable for Expression of Full Cofactor Activity in Activated Protein C-catalysed Inactivation of Factor Va and Factor VIIIa - Evenäs, Petra; García de Frutos, Pablo; Nicolaes, Gerry A. F.; Dahlbäck, Björn (Thrombosis and Haemostasis, 2000)
Vitamin K-dependent protein S is a cofactor to the anticoagulant serine protease activated protein C (APC) in the proteolytic inactivation of the procoagulant, activated factor V (FVa) and factor VIII (FVIIIa). In the FVa degradation, protein S selectively accelerates the cleavage at Arg306, having no effect on the Arg506 cleavage. In the FVIIIa inactivation, the APC-cofactor activity of protein S is synergistically potentiated by FV, which thus has the capacity to function both as a pro- and an anticoagulant protein. The SHBG-like region of protein S, containing two laminin G-type domains, is required for the combined action of protein S and FV. To elucidate whether both G domains in protein S are needed for expression of APC-cofactor activities, chimeras of human protein S were created in which the individual G domains were replaced by the corresponding domain of the homologous Gas6, which in itself has no anticoagulant activity. In a plasmabased assay, chimera I (G1 from Gas6) was as efficient as wild-type recombinant protein S, whereas chimera II (G2 from Gas6) was less effective. The synergistic cofactor activity with FV in the inactivation of FVIIIa was lost by the replacement of the G2 domain in protein S (chimera II). However, chimera I did not exert full APC-cofactor activity in the FVIIIa degradation, indicating involvement of both G domains or the entire SHBG-like region in this reaction. Chimera I was fully active in the degradation of FVa in contrast to chimera II, which exhibited reduced cofactor activity compared to protein S. In conclusion, by using protein S-Gas6 chimeric proteins, we have identified the G2 domain of protein S to be indispensable for an efficient inactivation of both FVIIIa and FVa, whereas the G1 domain was found not to be of direct importance in the FVa-inactivation experiments.
Keywords: APC-cofactor activity; factor V; G domains; protein S; SHBG-like region